Pulse corticosteroid therapy in the treatment of steroid-refractory immune checkpoint inhibitor-related pneumonitis: Case report and review - Lai, Kuan-Chang; Hsiao, Yi-Han; Chen, San-Chi (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICIs) have demonstrated promising therapeutic outcomes in treating a variety of malignancies, but immune-related adverse events (irAE) may develop. Among all the irAE, immune-related pneumonitis was relatively common and life- threatening. High dose corticosteroid was recommended for the initial management, but a part of patients developed steroid-refractory pneumonitis. Other immunosuppressants were recommended but the optimal treatment is still controversial. Here, we report two cases of steroid-refractory immune-related pneumonitis who were successfully treated with pulse corticosteroid therapy. Case 1 was hepatocellular carcinoma treated with nivolumab for 5 months. She developed acute respiratory distress syndrome due to grade 4 immune-related pneumonitis that was refractory to intravenous methylprednisolone 2 mg/kg/day treatment. Methylprednisolone 500 mg for 3 days followed by 2 mg/kg/day steroid as maintenance therapy was given. Subsequently, her pneumonitis was regressed, and the endotracheal tube was successfully removed on day 9 after the start of pulse therapy. Case 2 presented with grade 4 immune-related pneumonitis in spite the use of methylprednisolone 1 mg/kg for his skin rash. Pulse corticosteroid therapy was prescribed, then his pneumonitis was complete regressed on day 12. In this report, we demonstrated the potential role of pulse corticosteroid therapy for steroid-refractory pneumonitis.